Інтелектуальний капітал підприємства: комунікаційний аспект - Босак, А. О. (Видавництво Національного університету "Львівська політехніка", 2008)
Розглянуто низку проблем управління інтелектуальним капіталом (ІК) підприємства. Уточнено поняття "інтелектуальний капітал", "інтелектуальний потенціал", "інтелектуальні активи", "знання". Досліджено структуру ІК та визначено місце комунікацій у системі управління ІК. Виділено чинники, що впливають на рівень інтелектуального потенціалу та ефективність управління ІК. Проаналізовано методи оцінювання ІК. Досліджено вплив комунікацій на ефективність управління ІК підприємства. In the article the problems of intellectual capital management of enterprise are considered. The notions "intellectual capital", "intellectual potential", "intellectual assets", "knowledge" are elaborate. Structure of intellectual capital is explored and the place of communications in the managerial system by the intellectual capital is determined. Factors, influence upon the intellectual potential level and efficiency of intellectual capital management are chosen. Existing methods of intellectual capital valuing are analyzed. Influence of communications on efficiency of intellectual capital management of enterprise is explored.